STUDY OF APPROACHES, METHODS, SOURCES AND INTERPRETATION INSTRUMENTS OF MULLA SADRA - Moh. Nadhir Muâ'ammar (UIN Sunan Gunung Djati Bandung, 2019)
This research is carried out on some uniqueness found in the interpretation of the Al-Qur'an by Mulla Sadra, including: he is a philosopher who is the foremost in interpreting the Al-Qur'an and productive writers who have produced many works. In the hands of Mulla Sadra, the synthesis of the three Islamic intellectual schools, namely Sufi makrifat, philosophy or theosophy, and Shiite theology was finally reached, and directly reflected in the field of esoteric interpretation of the Al-Qur'an. Based on the uniqueness, the author is interested in examining it with the title: